17 Is not the right answer whats the right answer
Answer:
0.7
Step-by-step explanation:
Answer:
The equation is true.
Step-by-step explanation:
Simplify. Combine like terms:
3x + 15 = (2x + x) + (10 + 5)
3x + 15 = (3x) + 15
Isolate the variable, x. Note the equal sign, what you do to one side, you do to the other. Subtract 3x and 15 from both sides:
3x (-3x) + 15 (-15) = 3x (-3x) + 15 (-15)
3x - 3x = 15 - 15
0 = 0
~ True. The two expressions are equal to each other.
~
36 85
X 100
3600 = 85x
3600 divided by 85 =42.3529...